The presence and roles of English in Swedish print advertising: An exploratory study - Garcia-Yeste, Miguel (Nordic Journal of English Studies, 2024)
Despite the ubiquity of English in the Nordic societies, little attention seems to have been paid to the presence of English in advertising texts. Thus, the present study aims to survey the reality of the use of English in Swedish print advertising. A sample of advertisements published in Swedish magazines from different market segments is examined. Drawing on genre analysis and advertising research, this paper looks at the actual presence of English in this genre, at the moves that include English words and phrases, and at the values evoked by those expressions. The results suggest that English may not be so pervasive after all. Some of the roles and functions performed by English are discussed. Finally, questions to be addressed by future studies are presented.